Indicators of innovation and productivity in family farms: southern Mexico - Santiago Martinez , Gisela Margarita; Rodríguez Ortiz, Gerardo; Castañeda Hidalgo, Ernesto; Hernández Hernández, Beatriz Rebeca; Lozano Trejo, Salvador; Díaz García , Domingo Luis (Agricultura, Sociedad y Desarrollo, 2023)
Innovation is an opportunity to improve productivity and to achieve the development of marginalized communities. The objective of this study was to analyze the effect of innovation and productivity factors on the development of family farms (FFs) from marginalized localities in southern Mexico, under the systems approach. The study was non-experimental trans-sectional with a mixed approach and random stratified sampling. The indicator that interacted most with others was the farmer’s profile, defined by the type of crop in the FF that was independent of the locality, through the Kruskal-Wallis test (c2, 0.05) and Spearman’s correlation coefficient. Results show that FFs with greenhouse tomato innovate the most and generate greater economic satisfaction to the human factor, because of the productive system they implement. The interaction of factors implies the inexistence of knowledge that is strictly from the communities, since innovating and improving production requires a combination of influences, a type of crop and its aim, with the active participation of the farmer.